Ocean iron fertilisation beyond national jurisdiction: international law opportunities and constraint - Tunley, Karen (Institute of Marine and Environmental Law, 2026)
The concentration of greenhouse gases (GHG) in the atmosphere has increased substantially since the industrial revolution. Unequivocal evidence of a warming climate that has been observed includes increased global average air and ocean temperatures, extensive melting of snow and ice, and rising average sea levels. It is now generally accepted that the dominant cause of the climatic warming experienced is the increase in anthropogenic GHG emissions, most notably carbon dioxide (CO2). If mankind continues to emit GHGs at the current rate, by 2050 the concentration of GHGs in the atmosphere will have doubled pre-industrial levels and will most likely result in a global temperature increase exceeding 2°C.